2014
DOI: 10.1088/0957-4484/25/20/205605
|View full text |Cite
|
Sign up to set email alerts
|

Formation and phase transformation of Bi-containing QD-like clusters in annealed GaAsBi

Abstract: We report the formation and phase transformation of Bi-containing clusters in GaAs(1-x)Bi(x) epilayers upon annealing. The GaAs(1-x)Bi(x) layers were grown by molecular beam epitaxy under low (220 °C) and high (315 °C) temperatures and subsequently annealed using different temperatures and annealing times. Bi-containing clusters were identified only in the annealed samples that were grown at low temperature, revealing a relatively homogeneous size distribution. Depending on the annealing temperature and durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 30 publications
5
50
1
Order By: Relevance
“…EDX analysis performed on various droplet positions indicates that the droplet consists predominantly of Bi. In comparison, Bi-rich zincblende Ga(As, Bi) clusters and rhombohedral Bi clusters were reported for GaAsBi after annealing [21], and InBi clusters with distorted PbO structure were reported in InAsBi [22]. Such phase separation is attributed to the difficulties associated with Bi incorporation.…”
Section: Inas 1 à X Bi X Alloysmentioning
confidence: 99%
“…EDX analysis performed on various droplet positions indicates that the droplet consists predominantly of Bi. In comparison, Bi-rich zincblende Ga(As, Bi) clusters and rhombohedral Bi clusters were reported for GaAsBi after annealing [21], and InBi clusters with distorted PbO structure were reported in InAsBi [22]. Such phase separation is attributed to the difficulties associated with Bi incorporation.…”
Section: Inas 1 à X Bi X Alloysmentioning
confidence: 99%
“…They found that Bi atoms segregated to form anisotropic microstructures like pannikins [107]. Luna et al found lateral composition modulations (LCMs) by means of transmission electron microscope (TEM) [110]. The TEM images show that Bi atoms segregate to form quasi-periodical nano-columns along the growth direction.…”
Section: Segregationmentioning
confidence: 99%
“…The TEM images show that Bi atoms segregate to form quasi-periodical nano-columns along the growth direction. Wu et al also used TEM to observe phase segregation phenomenon in GaAsBi during annealing and found Bi clusters [110]. The phase was found to transform from ZB Bi-rich to rhombohedral-Bi in {111} continually until all the Bi atoms were consumed in the matrix.…”
Section: Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal annealing has been used to reduce the defects, but the incorporated Bi atoms often segregate and form Bi-rich clusters. 13 These defect-related issues have become a bottleneck in the successful applications of GaAsBi. For instance, to date, GaAsBi-based laser diodes require a threshold current density (2-10 kA cm − 2 ) 6,[14][15][16] that is approximately an order of magnitude higher than that of typical InGaAs-based laser diodes (0.2-0.5 kA cm − 2 ).…”
Section: Introductionmentioning
confidence: 99%